Clinical Interpretation of Efficacy Outcomes in Pharmacological Studies on Triple Fixed-Dose Combination Therapy for Uncontrolled Asthma: Assessment of IRIDIUM and ARGON Studies - Rogliani P; Calzetta L (Dove Medical Press, 2022)
Paola Rogliani,1 Luigino Calzetta2 1Unit of Respiratory Medicine, Department of Experimental Medicine, University of Rome "Tor Vergata", Rome, Italy; 2Department of Medicine and Surgery, Respiratory Disease and Lung Function Unit, University of Parma, Parma, ItalyCorrespondence: Paola RoglianiUnit of Respiratory Medicine, Department of Experimental Medicine, University of Rome "Tor Vergata", via Montpellier 1, Rome, 00133, ItalyTel +39 06 2090 4656Email paola.rogliani@uniroma2.itAbstract: The IRIDIUM and ARGON studies provided positive findings concerning the benefits of the once-daily triple mometasone furoate/indacaterol/glycopyrronium (MF/IND/GLY) fixed-dose combination (FDC) for the treatment of uncontrolled asthma, at the least by a strict statistical point of view. In the IRIDIUM study patients received medium-dose (MD) or high-dose (HD) MF/IND/GLY or MF/IND oncex daily or HD fluticasone/salmeterol (FLU/SAL) twice daily; in the ARGON study patients received MD or HD MF/IND/GLY once daily or HD FLU/SAL twice daily + tiotropium (TIO) once daily. Since a detailed interpretation of clinical results has not yet been performed, we provided the clinical interpretation of efficacy outcomes resulting from the IRIDIUM and ARGON studies according to the currently available minimal clinically important difference (MCID) thresholds. The triple MF/IND/GLY FDC elicited beneficial clinically relevant effects compared to active comparators in asthmatic patients, according to the levels of ICS doses, by generally achieving and overcoming the MCID. The level of clinical benefit was usually greater in patients treated with HD-MF/IND/GLY compared to those treated with MD-MF/IND/GLY. Overall, HD-MF/IND/GLY induced greater clinically relevant benefits even when compared to HD-FLU/SAL + TIO. Considering that a balanced triple MF/IND/GLY FDC with MD ICS resulted as effective as HD-MF/IND in preventing moderate or severe exacerbations, thus triple ICS/LABA/LAMA FDCs with MD ICS should be considered for the treatment not only of uncontrolled asthma but also for those patients suffering from less severe forms of disease with airflow limitation as well as a possible as-needed therapeutic option.Keywords: ARGON study, IRIDIUM study, minimal clinically important difference, MCID, triple therapy, uncontrolled asthma